(3GdeRGL dLGdjfhSs - (3LGdjfhSs
(3ChdgG (B:s
(3bO Hjf CaGVd GdbOeGA ef GdCWHGA hGdadGSaI HjGfkG cGajkG Cf CHOGf GdMjhGf eQcHI ef GdMGQ hGdHGQO hGdQWH s
(3BNQgG (B:s
(3aEfi GPG CVY ebGdI HGSQgG ai ShA GdeRGL GdeNJda , aEfG HPdc bO GSJcedfG bhdfG ai GdeRGL hCSJYjf ef Pdc Ydi WQjb GdMjdI ddHQA s
(3GfXQgG eY GdGSWbSGJs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B230 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdhWfjI HeOQjO (B(2/5011) s
Keywords: (3GdWHs